Prevalence of Abnormal Prenatal Screening for Down Syndrome in Udonthani Hospital Using Nuchal Translucency and Biochemical Marker - Songthamwat, Srisuda (Srinagarind Medical Journal, 2013)
Background : Down syndrome is the most common genetic cause of mental retardation . Prenatal screening test could be useful for early detection and provides the chance for termination of pregnancy or prepare the family to take care of their baby. Objective : To study the prevalence of positive results of prenatal screening for Down syndrome using Nuchal translucency and biochemical test in Udonthani hospital. Design : A descriptive study. Setting : Antenatal care clinic , Department of Obstetrics and Gynecology ,Udonthani hospital ,Udonthani. Subjects : Pregnant women who had their antenatal care at Udonthani Hospital from January 2005 to December 2007 Materials and Methods : Prenatal screening test for Down syndrome were performed in 314 pregnant women composed of 123 cases of Nuchal translucency measurement at 10-13 weeks of gestation and biochemical tests ( using PAPP-A plus Free beta hCG at 10-14 weeks of gestation or Maternal serum Alpha fetoprotein plus Free beta hCG between 15-20 weeks ) and biochemical tests only in 191 cases . Gestational ages were determined by ultrasonographic parameters . Genetic amniocentesis were offered to women with Nuchal translucency equal or more than 3 or calculated down syndrome risk of 1 :270 or greater and to women aged 35 years or over Babies data were followed after birth in both screening and non screening group . Results : Prevalence of positive screening tests were 9.6 % (30/314) composed of Nuchal translucency more than or equal to 3 mms 2.4 % ( 3 /123) and 8.9 % (28/314) of abnormal biochemical test ( risk greater than or equal to 270 ) . All of positive screening test were received genetic amniocentesis and 1 case (3.3 %) of trisomy 21 was detected , All of negative screening cases wered followed and 1 case of trisomy 21 was found (in low risk group) . Detection rate of our screening test is 50 % and false positive rate is 9.3 % Conclusion : Maternal screening using nuchal translucency and biochemical test is effective in the detection of fetal down syndrome and possibly one chioce for pregnant women especially in low risk group.